O mediador de conflitos como intérprete das partes: uma análise à luz da teoria do agir comunicativo - Munhoz, Elisangela Peña (2015)
This research explores the mediator's role conflict to the Habermas´s Theory of communicative action. The matter has gained repercussion with justice access movement in Brazil. The Right structured by the laws, by theory and by an established practice procedurally welcomed the mediation. However, this is a practice that runs the formalities of the legal context. The opportunity for this research is the complex task of conducting a dialogue to transform a conflict situation without the support of the coercive and decision-making power of a sentence. Researchers and activist urges for the initiative of mediation in face of the need for adjustments of the instrumental form and technique that has traditionally been established by law, but that does not meet the specific demands of mediation. The proposal is to institute the construction of the mediator's role in the field of communication, to experience in practice the benefits offered by the communicative action. Our goal is to review how the legal sciences perceive the role of mediator. Habermasians comprehend that the mediator works is to build a communicative situation; therefore the purpose is that it should be regarded as an interpreter of the conflicting parties. Elected as corpus three foreign models, the North American, Italian and Argentinian, to deconstruct them in order to understand its structures and treat critically its constituent aspects. The mediator´s is the dialogue´s leading figure, using an explanatory speech to clarify the points that are causing the conflict. He does not aim to solve the conflict, but it is willing to provide the mediated sides another chance to talk. Since the bridge between theory and praxis is established with the help of Eric Landowski´s semiotic regimes of interaction. Studies of the French semiotician and sociologist indicate that mediation relies on the human ability to aesthesia, the actant´s ability to perceive each other, for both to engaee each other in a collaborative construction. The conflict, with the contribution of Axel Honneth has revealed something to social own latent social interaction. Therefore it is needed to address the risks inherent in mediation. This exercise is done under three perspectives: the risks from the perspective of relationship, the mediator himself and the mediated. The research consists of three stages: in the first chapter, we treat the mediation under the historical and rational aspects, in parallel with the theory of modernity; in the second, we treat the theory of communicative action and the concept of access to justice; in the third, we rethink the role of mediator